Cutaneous mycobacterium abscessus infection associated with mesotherapy injection - Pranee Wongkitisophon (2018)
Non-tuberculous mycobacterial skin infections have an increasing incidence. In immunocompetent patients, they usually follow local trauma. We present a case of cutaneous Mycobacterium abscessus infection following mesotherapy. The lesions were successfully treated with a combination of clarithromycin, ciprofloxacin, and doxycycline. Atypical mycobacterial infection should be suspected in patients who develop late-onset skin and soft tissue infection after cutaneous injury, injection, and surgical intervention, particularly if they do not respond to conventional antibiotic treatment. Copyright © 2011 S. Karger AG, Basel.